LEE-CARTER MODELING FOR MORTALITY IN INDONESIA WITH A BAYESIAN APPROACH - Fajar, Muhammad; Fajariyanto, Eko (PATTIMURA UNIVERSITY, 2022)
This study aims to model Lee-Carter mortality with a Bayesian approach, where the parameters in the model are assumed to be random variables. The data used in this study is data on mortality rates by age group from the period 1950–2015. The sourced of data was from the UN website. Age groups are categorized by age 0 years, 1-5 years, 6-10 years, 11-15 years, ..., 86-90 years. The results of this study are from Bayes estimation obtained information that the average infant mortality rate (population aged less than one year) is high, then at the age of toddlers (1-4 years) average mortality rate decreases. Furthermore, the average mortality rate for children, adolescents, young and older people has increased again. Meanwhile, the relative speed of the pattern of changes in mortality at infant age (less than one year) is high enough. At the age of toddlers (1 – 4 years), the pattern of changes in mortality has increased. Then, in the population of the next age group until the older age group, the mortality continues to decrease. The pattern of changes in mortality is lowest in the elderly population.